The impact of applying the continuous improvement budget on administrative decisions in Iraqi companies - sabar Khasheef, abdulameer (Iraqi Journal for Administrative Sciences, 2024)
The research dealt with the possibility of applying the continuous improvement budget in Iraqi companies, and its impact on administrative decisions in light of the traditional system and the Japanese (Kaizen) system. As well as the role that planning budgets play in the administrative decisions of companies in light of the current electronic environment. The research reached many results, including that the developments that occurred in the current business environment as a result of increased global competition and progress in manufacturing technology made it difficult for companies to survive, but to respond to these changes and achieve customer satisfaction by any means. The researcher recommends the necessity of a vigorous approach by Iraqi companies to modernize their production programs and to benefit from the experiences of international companies in the field of using modern production and administrative techniques, as well as working to change the culture of their employees towards the continuous development and improvement of their companies in order to compete. In light of the orientations of the Iraqi market towards the free market.